PEREMPUAN BERGERAK Surat Kabar Soenting Melajoe 1912-1921 - Danil M. Chaniago (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Soenting Melajoe is the first womens newspaper published in the Minangkabau and the mission is to improve the quality and degree of women. Newspaper which was published in 1912 is a reflection of the social movement in the Minangkabau women fighting for and achieving their rights without going out of their natures as the “keeper” in his household. Despite the challenge is great enough of Minangkabau society, “Bundo Kanduang” is not decreased in bringing about social change in Minangkabau until the end of its publication in 1921. Keywords: Newspaper, women and social change Copyright © 2014 by Kafa`ah All right reservedDOI : 10.15548/jk.v4i1.90